11x-39=6x+26

Simple and best practice solution for 11x-39=6x+26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x-39=6x+26 equation:


Simplifying
11x + -39 = 6x + 26

Reorder the terms:
-39 + 11x = 6x + 26

Reorder the terms:
-39 + 11x = 26 + 6x

Solving
-39 + 11x = 26 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-39 + 11x + -6x = 26 + 6x + -6x

Combine like terms: 11x + -6x = 5x
-39 + 5x = 26 + 6x + -6x

Combine like terms: 6x + -6x = 0
-39 + 5x = 26 + 0
-39 + 5x = 26

Add '39' to each side of the equation.
-39 + 39 + 5x = 26 + 39

Combine like terms: -39 + 39 = 0
0 + 5x = 26 + 39
5x = 26 + 39

Combine like terms: 26 + 39 = 65
5x = 65

Divide each side by '5'.
x = 13

Simplifying
x = 13

See similar equations:

| p^2-14p-31=0 | | x=15-0.6x | | 24x+4=20x-8 | | sec^2x-6=-4 | | 6(3x-7)-6=6(x-3)+54 | | 8u+2u=3u | | (180/165)=n/(n-2) | | 2x+16=38 | | 8-(4x+7m)=5(x+6)-2 | | 0.40(x+80)+0.80x=68 | | 13x-(4x-6)=60 | | 3/8=2/2 | | -10=-8+6x-2 | | 4-3x=-3x+6 | | f(3)=-2(3)+5 | | 9x+3=17x | | 21x-26=23x-9 | | -5(1+6n)=10 | | -3(3s-3)-9=-2(8s+6)-2 | | Y+20=10(x+9) | | 6x-256=2 | | -4x^2+x-3=0 | | .90x+0.05(6-x)=0.10(71) | | 10n+100-10=600 | | 7x^2+12x=y^2 | | (8/9)×(6/7)= | | 500x+800y=11500 | | .36(18)+.06x=0.12(24+x) | | -24n^10+3n=0 | | 8-3(x-4)=2x+5 | | 22-5x=2x-13 | | 15x-15=-12x |

Equations solver categories